2019
DOI: 10.1039/c8mt00317c
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanides compete with calcium for binding to cadherins and inhibit cadherin-mediated cell adhesion

Abstract: Substitutions with lanthanides reveal a high sensitivity of cadherin structure, dynamics and function to metal ion chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…Upon concluding that the proteins were not obtainable in a Ca 2+ -free form without the addition of EDTA or EGTA, we decided to indirectly estimate the affinity of the proteins to Ca 2+ by measuring the binding of terbium(III) ions (Tb 3+ ), as Ca 2+ -binding proteins can also bind lanthanide ions due to similar effective ionic radii and positive charges of Ca 2+ and lanthanide ions 39 . The binding of lanthanide ions by Ca 2+ -binding proteins is usually stronger than the binding of Ca 2+ , due mainly to a higher positive charge 40 42 . Therefore, protein-bound Ca 2+ should be substituted by Tb 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Upon concluding that the proteins were not obtainable in a Ca 2+ -free form without the addition of EDTA or EGTA, we decided to indirectly estimate the affinity of the proteins to Ca 2+ by measuring the binding of terbium(III) ions (Tb 3+ ), as Ca 2+ -binding proteins can also bind lanthanide ions due to similar effective ionic radii and positive charges of Ca 2+ and lanthanide ions 39 . The binding of lanthanide ions by Ca 2+ -binding proteins is usually stronger than the binding of Ca 2+ , due mainly to a higher positive charge 40 42 . Therefore, protein-bound Ca 2+ should be substituted by Tb 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have suggested positive impacts of RE provision in animal husbandry, suggesting a role for REs in higher organisms. 128 However, REs are not perfect mimics of Ca, 4 as recent studies of calmodulin 129,130 and cadherin 131 have shown, suggesting that REs may not play a general role as Ca substitutes in Ca-dependent proteins. Instead, the growth-promoting effects of REs in higher organisms might plausibly be linked to the microbiome; for example, both beneficial ( E. coli ) and pathogenic ( Pseudomonas aeruginosa ) bacteria possess PQQ-dependent dehydrogenases, and these or other enzymes might benefit from or be inhibited by REs.…”
Section: Lanthanides Beyond Bacteriamentioning
confidence: 99%
“…[12][13][14][15][16] To avoid the cytotoxicity of free metal ions, which is mainly caused by binding to endogenous metalloproteins and subsequent structure disruption, the metals are tightly complexed with multidentate ligands. [17][18][19][20] The most prominent chelators are the macrocyclic 1,4,7,10-tetraazacyclododecane-1,4,7,10tetraacetate (DOTA) and its analogs ( Fig. 1).…”
Section: Lanthanide Conjugates In Diagnostics and Therapymentioning
confidence: 99%